Modulating the Inclusive and Coordinating Ability of Thiacalix[4]arene and Its Antenna Effect on Yb3-Luminescence via Upper-Rim Substitution+ - Sergey N. Podyachev; Svetlana N. Sudakova; Rustem R. Zairov; Victor V. Syakaev; Alexey N. Masliy; Michal Dusek; Aidar T. Gubaidullin; Alexey P. Dovzhenko; Daina N. Buzyurova; Dmitry V. Lapaev; Gulnaz Sh. Mambetova; Vasily M. Babaev; et al. (Molecules, 2022)
The present work introduces the series of thiacalix[4]arenes (H4L) bearing different upper-rim substituents (R = H, Br, NO2) for rational design of ligands providing an antenna-effect on the NIR Yb3+-centered luminescence of their Yb3+ complexes. The unusual inclusive self-assembly of H3L− (Br) through Br<semantics>π</semantics> interactions is revealed through single-crystal XRD analysis. Thermodynamically favorable formation of dimeric complexes [2Yb3+:2HL3−] leads to efficient sensitizing of the Yb3+ luminescence for H4L (Br, NO2), while poor sensitizing is observed for ligand H4L (H). X-ray analysis of the single crystal separated from the basified DMF solutions of YbCl3 and H4L(NO2) has revealed the transformation of the dimeric complexes into [4Yb3+:2L4−] ones with a cubane-like cluster structure. The luminescence characteristics of the complexes in the solutions reveal the peculiar antenna effect of H4L(R = NO2), where the triplet level at 567 nm (17,637 cm−1) arisen from ILCT provides efficient sensitizing of the Yb3+ luminescence.